Exploring Math Anxiety Towards the Students’ Computer Self-Efficacy in Learning Mathematics - Dilla Amelia Zay; Meyta Dwi Kurniasih (Mosharafa: Jurnal Pendidikan Matematika, 2023)
AbstrakDi tengah pandemi Covid-19, siswa dituntut menguasai penggunaan komputer dalam pembelajaran matematika daring. Tingkat efikasi diri yang tinggi dapat secara signifikan mengurangi kecemasan matematika siswa dan sebaliknya. Tujuan penelitian ini adalah untuk mengetahui tingkat kecemasan matematis terhadap efikasi diri komputer dalam pembelajaran matematika, dan mengetahui hubungan antara kecemasan matematis terhadap efikasi diri komputer. Penelitian kuantitatif ini menggunakan survei untuk mengumpulkan data. Partisipan dipilih dengan menggunakan probability sampling. Angket berisi 25 soal juga diberikan kepada 200 siswa kelas 8 MTSN 7 Model Ciracas. Hasil penelitian menunjukkan bahwa seluruh indikator pada variabel kecemasan matematika menunjukkan skor rata-rata sedang dengan skor rata-rata tertinggi (3,14). Rata-rata efikasi diri komputer masih tergolong sedang dengan indikator tingkat besaran (????̅= 2,97) sebagai nilai rata-rata tertinggi. Nilai koefisien korelasi sebesar -0,193 menunjukkan adanya hubungan negatif yang signifikan dengan derajat korelasi yang dapat diabaikan. AbstractAmidst Covid-19 pandemic, students were required to master the use of computers in online mathematics learning. High level of self-efficacy could significantly reduce students’ math anxiety and vice versa. The purpose of this study was to determine the level of mathematical anxiety towards computer self-efficacy in learning mathematics, and investigate the relationship between mathematical anxiety towards computer self-efficacy. This quantitative study used survey to collect the data. The participants were selected by using a probability sampling. A questionnaire containing 25 questions were also given to 200 students in 8th grades at MTSN 7 Model Ciracas. The results revealed that all indicators in the mathematics anxiety variable showed a moderate average score with the highest average score (3.14). The average of computer self-efficacy was still moderate with a magnitude level indicator (????̅= 2,97) as the highest average value. The correlation coefficient value was -0.193 implying that there was a significantly negative relationship with a negligible degree of correlation.